The relationship between - naiema khodadady; farzaneh shikholeslami; shohreh ahmadi; aliyeh FARZAM; zahra sharif (Guilan University of Medical Sciences, 2008)
Introduction: Schizophrenia is a common and chronic mental disorder. Many of ‎Schizophrenia clients for some reasons stop taking anti psychotic drugs which results in ‎relapse and repeated hospitalizations, inability to keep a job and stigmatization and it can ‎decrease their quality of life. In attention to the point that follow up care at home can effect ‎clients' QOL, this study is designed to surcey it.‎ Objective: This study aims to determine the relationship between "home follow up" care and ‎quality of life in clients with schizophrenia reffering to health centers in Rasht in ‎‏2006‏‎.‎ Methods: This was a descriptive study with ‎‏29‏‎ patients with schizophrenia attending a ‎psychiatry outpatient clinic,using a convenience sampling in Rasht. In addition, a sample of ‎‏23‏‎ patients with home follow up were selected from the home visit list who had the inclusion ‎criteria. Socio-demographic questionnaire and standard questionnaire of QOL were completed ‎through face to face interview.‎ Results: From the total ‎‏52‏‎ participants in this study, most were single and unemployed. There ‎was a statistically significant relationship between home follow up and statement of quality ‎of life (p<‎‏0.005‏‎), satisfaction with health (p<‎‏0.001‏‎), satisfaction with sleep ( p< ‎‏0.01‏‎) and ‎satisfaction with home environmenr (p<‎‏0.049‏‎). ‎ Conclusion: The findings suggest that patients with schizophrenia underlie home follow up ‎have high quality of life in Rasht city.‎